Inhibition of murine fibrocyte differentiation by cross-linked IgG is dependent on FcγRI. Issue 2 (21st April 2014) - Pilling, Darrell; Crawford, Jeffrey R; Verbeek, J Sjef; Gomer, Richard H
Abstract : FcγRI (CD64) mediates the inhibitory effects of cross-linked IgG on murine fibrocytes. Abstract: Monocyte-derived, fibroblast-like cells, called fibrocytes, participate in wound-healing and the formation of fibrotic lesions. Aggregated or cross-linked IgG are key effectors in infections, autoimmune diseases, anaphylaxis, and immunotherapy. Cells, including monocytes and fibrocytes, bind IgG using FcγRs, and aggregated or cross-linked IgG inhibits fibrocyte differentiation. Mice have four different FcγRs, and which of these, if any, mediate the cross-linked IgG effect on fibrocyte differentiation is unknown. We find that in mice, deletion of FcγRI or the common signaling protein FcRγ significantly reduces the ability of cross-linked IgG or IgG2a to inhibit fibrocyte differentiation. Cells from FcγRIIb/III/IV KO mice are still sensitive to cross-linked IgG, whereas cells from FcγRI/IIb/III/IV KO mice are insensitive to cross-linked IgG. These observations suggest that IgG-mediated inhibition of fibrocyte differentiation is mediated by FcγRs, with FcγRI mediating most of the signaling.